An integrated chronological study on the Quaternary sedimentary sequences of the Yangtze River delta, China - Li, Guomin; Ji, Wenting; Xiao, Guoqiao; Xu, Huiru; Liang, Yuan; Lai, Yiming; Du, Jianguo; Li, Xiangqian; Wu, Jianqiang (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
The sedimentary sequences of the Yangtze River delta comprise important Quaternary records of tectonics, sea-level oscillation, and climatic change; however, analysis is hampered by a lack of a reliable chronological framework. In this paper, we present an integrated chronology for two sedimentary sequences (core ZKW2 and ZKW4) on the southern side of the Yangtze River delta, based on magnetostratigraphy and absolute methods (OSL, 14C, and ESR dating). The basal ages of the core ZKW2 and ZKW4 are ca. 2.25 Ma and 2.96 Ma, respectively. The integrated chronology indicates significant increases in the sedimentary accumulation rate at ∼0.15 Ma, rather than the Matuyama-Brunhes boundary as indicated by magnetostratigraphy alone. The observed sedimentary transition is possibly controlled by regional subsidence of the Zhe-Min Uplift, and climate evolution during the last interglacial period. •High-quality magnetostratigraphy is obtained for the Quaternary sediments in the YRD.•The SARs of the YRD sediments significantly enhanced since ∼0.15 Ma.•Tectonics and climate factors jointly control the sedimentary evolution in the YRD.